El Sur Tambien Existe - Becu, Nuria (Argentina : Junco Films Juan Manuel Biain, 2008)
This investigative documentary looks at the differences in educational standards between the state-run schools located in the affluent Northern and the disadvantaged Southern localities of Buenos Aires. At huge personal risk, the teachers themselves see no other way of improving the student's desperate situation than blowing the whistle on their public employers by telling their own story and exposing the issues they face on a daily basis. The film creates a distressing portrait of the systematic socio-economic discrimination that takes place within the public school system and is depriving thousands of children of a valuable education and a way out of poverty.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films